IN VITRO PROPAGATION OF "CRITICALLY ENDANGERED" MEDICINAL PLANT-ASPARAGUS RACEMOSUS - ANURAG JAIN; KRISHAN KUMAR (International Journal of Pharma and Bio Sciences, 2013)
Asparagus racemosus is an herb used as a rasayana in Ayurveda. The root of A racemosus is popular for its various medicinal uses such as appetizer, stomachic, tonic aphrodisiac galactogogus etc. In this experiment we have found the shoot induction after 3 weeks when Nodal explants segments were cultured in basal medium supplemented with BAP, Kin and Ads and Shoots induction on MS basal medium supplemented with BAP + kin were transferred to MS basal medium containing BAP + Ads and BAP + Kin respectively to the Proliferation shoots. Stem segments cultured on MS basal medium supplemented with various concentrations of BAP, AdS and Kin induce shoot, But a combination of BAP + Kin and BAP + Ads showed the highest percentage of shoot proliferation after 7-14 days. The elongated shoots (3-4 cm length) derived from MS Basal medium supplemented with BAP & ADS were excised and Transferred to MS medium containing NAA + BAP + kin and BAP + NAA for rooting. But a combination of NAA + BAP + Kin showed highest percentage of root formation within7-10 days. Eighty percent of shoots produced well developed roots in 15-20 days when MS medium was supplemented with NAA (1.0mg/l). Highest callus induction from nodal explants was found best in combination of 1.0 mg/L NAA + 1.0 mg/L 2,4-D + 0.5 mg/L BAP.